Nutrient omission and nutritional status of young Theobroma grandiflorum plants - Galvão, Jessivaldo Rodrigues; Viégas, Ismael de Jesus Matos; Maia, Bruno Kleidson da Silva; Botelho, Anderson de Santana; do Amarante, Cristine Bastos; Canuto, Matheus Gustavo dos Santos; Da Silva Júnior, Luiz Eduardo Freitas; Farias, Thaysa Helena Alves (Comunicata Scientiae, 2025)
The cupuaçu tree (Theobroma grandiflorum (Willd. ex Spreng.) Schum.), belonging to the Malvaceae family, is one of the most important and popular fruit species in the Amazon. With the growth of commercial production and the increasing demand for seedlings, research aimed at optimizing its cultivation has become essential. Therefore, this study aimed to evaluate the development of young cupuaçu plants subjected to nutrient omission. The experiment was conducted under greenhouse conditions at Embrapa Eastern Amazon. The soil used was a Yellow Latosol of medium texture, collected from a depth of 0–20 cm. The experimental design was completely randomized with 10 treatments: complete (macro- and micronutrients); omission of N, P, K, Ca, Mg, S, B, and Zn; and a control treatment, with five replications. The evaluated variables included plant height, stem diameter, number of leaves, leaf area, dry matter production (leaves, stems, branches, and roots), macro- and micronutrient contents, and leaf analysis. To compare means, the Scott-Knott test at a 5% probability level was applied, following significance by the F test. Overall, nutrient omission limited plant development; however, the most detrimental to plant growth were N, P, K, Mg, and S. These same nutrients (with the exception of Mg) were also those that most affected total dry matter. It was concluded that young cupuaçu plants cultivated in medium-textured Yellow Latosol soils have high demands for macronutrients and the micronutrients B and Zn to achieve optimal development.